Interior Accessibility of the Sang Nila Utama Museum in the Framework of Universal Design and Spatial Experience - Ravelino, Parlindungan; Kusmara , Andryanto Rikrik; Adhitama, Gregorius Prasetyo; Malasan, Prananda Luffiansyah (Jurnal Riset Arsitektur, 2025)
Most museums in Indonesia have not fully implemented universal accessibility principles, resulting in spatial experiences that are not yet inclusive for persons with disabilities and other vulnerable groups. Sang Nila Utama Museum in Pekanbaru, a type C museum representing Riau Malay culture, illustrates the gap between educational aspirations and the reality of accessibility. This study aims to evaluate the application of Universal Design principles and interpret visitors’ spatial experiences through multisensory and phenomenological perspectives. A descriptive qualitative approach was employed through reflective observation and visual documentation in the field. Accessibility was analyzed using the Seven Principles of Universal Design, while sensory experience was interpreted using a phenomenological framework. The findings show that physical facilities such as ramps, toilets, signage, and circulation paths do not meet minimum accessibility standards. Spatial experience remains predominantly visual, with limited tactile, auditory, and olfactory engagement. These findings highlight a significant gap between accessibility regulations and the actual experiences of visitors in regional museums. Museum inclusivity depends not only on physical access but also on sensory justice and equitable spatial experience. This study offers an integrated model combining Universal Design and multisensory phenomenology as a reference for improving the interior design of regional museums in Indonesia.